GAMBARAN PELAKSANAAN BEDSIDE TEACHING PADA PRAKTIK KLINIK KEBIDANAN PRODI KEBIDANAN JENJANG DIPLOMA III STIKES 'AISYIYAH YOGYAKARTA - Rosmita Nuzuliana; Kharisah Diniyah; Esitra Herfanda (Universitas Aisyiyah Yogyakarta, 2015)
The purpose of this research is to find out the Implementation of bedside teaching (BST) in clinical practice. We used observational analitic with cross sectional approach and total sampling technique. The samples are Diploma level midwifery students who have completed all the clinical practice of obstetrics and all activities in the academic year 2014/2015. We used 162 respondents. The result showed that all respondents are female, and the average age of respondents was 21 years. BST Implementation on average get good grades from students. A total of 61.11% of the students stated BST delivered well and easily understood. Average stage in the implementation of the BST gets good grades from students. The alocated time given by mentors for BTS implementation received moderate ratings from students, which is 68.52%.Keywords: bedside teaching, midwifery clinical practice, midwifery students